Dzikrullah: religious therapy for treating individuals with neurasthenia disorders - Syaifatul Jannah, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2024)
This study is about the application of the dzikrullah technique as a strategy for providing religious therapy services to treat individuals with neurasthenic disorders. The pleasures of the world and the neglect of religious obligations carried out by most of today’s Generation Z youth raise various kinds of problems, making them more susceptible to neurotic disorders, one of which is neurasthenic disorder. Neurasthenia is a condition characterized by chronic physical and mental fatigue, even though no physical causes are found. This condition can hinder the development of adolescents, making treatment necessary for them to develop and grow while maintaining a healthy mentality, namely through religious therapy using the dzikrullah technique. The research method uses a qualitative approach, with the type of case study, and the data collection methods used are interviews, observations, and documentation. The results showed that religious therapy with the dzikrullah technique was successful in dealing with individuals with neurasthenia disorders, which were characterized by a calmer heart condition. The dzikrullah technique applied includes three interventions: therapy to eliminate all anxiety, sadness, depressed feelings, mental unrest, inner conflict, anxiety; therapy to eliminate fear; and therapy to cure insomnia.